2019
DOI: 10.1021/acschembio.8b00916
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Retinoic Acid Analogues as Probes for Biochemical and Intracellular Characterization of Retinoid Signaling Pathways

Abstract: Retinoids, such as all-trans-retinoic acid (ATRA), are endogenous signaling molecules derived from vitamin A that influence a variety of cellular processes through mediation of transcription events in the cell nucleus. Because of these wide-ranging and powerful biological activities, retinoids have emerged as therapeutic candidates of enormous potential. However, their use has been limited, to date, due to a lack of understanding of the complex and intricate signaling pathways that they control. We have design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Pohl et al reported fluorescent retinoids targeting cellular retinoid binding protein II (CRABPII) 26,27 .…”
Section: Resultsmentioning
confidence: 99%
“…Pohl et al reported fluorescent retinoids targeting cellular retinoid binding protein II (CRABPII) 26,27 .…”
Section: Resultsmentioning
confidence: 99%
“…All of the compounds exhibited photophysical properties (Table 1) that were characteristic of other donor-acceptor diphenylacetylenes. 16,17,19 The compounds exhibited absorption (Fig. 2, Table 1 and ESI Section 2) bands at around 300 nm (S0 → S2) and 360-400 nm (S0 → S1) due to the formation of intramolecular charge transfer excited states as a result of the presence of strong π-donor/acceptor moieties (Figure 2A).…”
Section: Photophysical Characterisationmentioning
confidence: 99%
“…EC23, DC324 and DC360 ( Figure 1) were synthesized according to the published procedures [12][13][14][15]. EC23 and DC360 are synthetic analogues of ATRA, and DC324 is a nonactive analogue that exhibits poor binding affinity for the retinoic acid receptors due to the compound's extended structure.…”
Section: Synthetic Retinoidsmentioning
confidence: 99%